A modified FSDT-based four nodes finite shell element for thermal buckling analysis of functionally graded plates and cylindrical shells. (1st January 2019) - Trabelsi, S.; Frikha, A.; Zghal, S.; Dammak, F.
Highlights: Thermal buckling analysis of FGM plates and cylindrical shells are investigated. Finite element formulation based on a modified FSDT shell formulation is elaborated. Introduction of parabolic distribution of transverse shear strains. Applicability and usefulness of the present formulation is highlighted through numerical simulations. Abstract: In this paper, the thermal buckling behavior of functionally graded plates and cylindrical shells is investigated. By considering a modified First order Shear Deformation Theory, the governing equations are elaborated. The kernel idea of the proposed model consists on assuming a parabolic distribution of the transverse shear strains across the shell thickness and imposing a zero condition of the transverse shear stresses on the top and bottom surfaces of the shell structure. Four nodes shell elements are adopted to solve the thermal buckling problem. The material properties are assumed to change continuously through the thickness according to a power-law distribution. In order to highlight the potentials of the present formulation, numerical investigations are conducted and compared with results available from the literature. The computation of the critical buckling temperature of structures under non-uniform temperature rise is based on Gauss numerical integration. The effects of material compositions, power law index, thermal loading, boundary conditions and geometrical parameters of shells on the thermal buckling behavior of FGM structures are also examined.